Science of stretch : reach your flexible potential, stay active, maximize mobility - Malek, Leada (New York, NY : DK Publishing, 2023)
"Fight back against sedentary living with stretch workouts to extend mobility, increase strength, and support fitness. Loosen up tight muscles and stiff joints with more than 100 stretches designed to keep you flexible, extend mobility, and support fitness. As home working becomes the new normal, and as we get older, we are all at risk of seizing up, losing muscle functionality, and developing aches and pains from increased sedentary living. And to support the regular exercise that is so vital to health at any age, we need to maintain a full range of motion, and help to alleviate joint and muscle stiffness. With a regular programme of varied stretch workouts, everyone can reach and support their maximum mobility. Look no further than Science of Stretch for a complete home course in stretching, no gym membership required. Discover the latest scientific research on the benefits of different modes of stretching, and learn how best to integrate them into your day, alongside warm-ups and exercise sessions. With detailed, annotated artworks demonstrating the most effective stretches for every part of the body and stretch routines tailored to different abilities and fitness objectives, Science of Stretch will help you maintain the fullest range of motion, keep active, and optimize the benefits of stretching to both body and mind"--
Preface -- Introduction -- Physiology of stretching -- Stretch exercises. Neck and spine exercises ; Shoulder, arm, and hand exercises ; Hip exercises ; Leg and foot exercises ; Nerve mobility exercises -- Stretch routines.
At head of title: DK.
Includes bibliographical references (pages 218-222) and index.
Keywords: Stretching exercises; Pain -- Physical therapy; Self-care, Health; SCIENCE / Life Sciences / Human Anatomy & Physiology; Stretching exercises; Instructional and educational works